Le développement expérimental en situation de projet - Stéphane Berthier (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Research and development (R&D) activity helps to consolidate the work of fundamental research, applied research, and experimental development - the latter dealing with experimental work practice obtained at pilot installations or prototypes. This article seeks to explore this notion of applied experimental development within architecture through the examination of three detailed projects from Lipsky + Rollet’s agency which are: Student housing on Troyes campus, the Indian House at La Cité Universitaire de Paris, and the “Positive Habitat” competition in Bologne. Each of these projects explore different means of innovative construction, all of which use wood as their primary building material and experiment with its technical, physical and ecological qualities. The work of these architects poses research enquiries about the compatibility between construction materials that were initially developed in isolation from their reciprocal industrial sectors. These prefab technical sub-assemblies must find their place within the complexities of architectural projects which are assembled based on their own rules and objectives. According to Edgar Morin’s formula, a company that no longer experiments is no longer innovative and must therefore import other models externally, making this step in situational prototyping of projects crucial. This experimental activity creates a tool for knowledge out of architectural projects and thus the edifice should no longer be understood as a simple domain for applying upstream elaborated technical solutions, rather as an experimental milieu which is necessary for its development. Its purpose is to bring diverse systems and original constructive means to architectural synergies as well as possible techniques that have yet to be seen together in fundamental and applied research domains. The example of Lipsky + Rollet’s work shows us what could be a form of R&D particular to architecture for those who have managed to reform unsuitable professional frameworks and to explicitly render its methods accordingly.